Rate of Return Regulation in the sector of electronic communications - O. I. Pizhuk (Економіка, управління та адміністрування)
The introduction of regulation of the rate of return in the electronic communications sector is a decisive step towards realizing our country's digital ambitions and harnessing the transformative potential of modern digital technologies. The article justifies the relevance of such a step in the context of Ukraine's commitments regarding domestic electronic harmonization of the communications market with EU requirements, particularly aimed at supporting market stability and enhancing the well-being of end consumers.